Cambridge Illustrated Glossary of Botanical Terms - Hickey, Michael; King, Clive (Cambridge : C U P, 2000)
This beautifully illustrated glossary constitutes an extraordinary collection of the specialist terms used in many botanical works. The book is arranged in two sections: the glossary, which provides clear definitions for over 2400 of the most commonly used botanical and horticultural terms, and illustrations, which can be cross-referenced to the glossary. The illustrations section comprises over 120 large format pages packed with accurate, well labelled line drawings that complement the definitions. The illustrations are grouped according to specific features, allowing quick comparisons of different forms. This outstanding reference will be welcomed by all readers grappling with botanical terms, whether student, professional, or hobbyist.
Keywords: Botanical terms; Glossary; Botany